Globalization of The Journal of Craniofacial Surgery Over The Last Decade: A Continent, Country, and State Level Analysis. Issue 3 (May 2021) - Liechty, Andrew E.; O'Rorke, Erin V.; French, Mackenzie M.; Vu, Giap H.; Robinson, Emily M.; Cho, Daniel Y.; Friedrich, Jeffrey B.; Susarla, Srinvas M.
Abstract : Abstract: Craniofacial surgery continues to be a rapidly evolving field, due in part to interdisciplinary collaboration that has allowed for sharing of knowledge and methodologies, which has expanded greatly due to online journals and publications. The Journal of Craniofacial Surgery (JCS) is a highly regarded journal that has attracted attention for its mission to increase diversity and global representation in manuscript submissions and research publications. The purpose of this study is to provide an objective measurement of global participation in craniofacial research specifically as it pertains to the JCS. Through a bibliometric analysis, the country of origin of all articles published in the JCS from 2010 to 2019 was analyzed. In line with its mission, the JCS increased its overall production 1.9 times during the past decade and increased its global representation 1.6 times, as represented by the number of countries contributing (78). The journal produced 8147 articles with Turkey (1424), USA (1397), China (1178), South Korea (1023), and Italy (644) being the top producers. The highest represented states were Florida (156), New York (130), California (117), Massachusetts (112), and Pennsylvania (106). The Journal of Craniofacial Surgery has the greatest diversity of country representation of the major plastic and reconstructive journals compared. Overall the JCS has stayed true to its mission to foster craniofacial research and is a valuable resource for craniofacial surgeons across the world. This study provides an analysis of trends in global contributions to craniofacial research and highlights areas for further increasing global contributors to the field of craniofacial surgery. Abstract : Supplemental Digital Content is available in the text